1998
DOI: 10.1007/s004420050475
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar abundance in the territory affects the breeding performance of great tit Parus major minor

Abstract: The effects of caterpillar food supply on the breeding performance of a population of the Japanese great tit Parus major minor were investigated. Since more than 90% of the food items in our study site were caterpillars living on trees, we estimated the food availability using 20 frass traps per hectare. The sampling error of this method was about 10% on average, which was accurate enough to detect differences between territories. Food abundance at laying in each territory affected the timing of egg laying. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 18 publications
1
32
0
3
Order By: Relevance
“…Many designs of frass trap have been published (Liebhold & Elkington 1988, Seki & Takano 1998, Tinbergen 1960, Tinbergen & Dietz 1994, Zandt 1994, but in this study we deployed simple, inexpensive traps consisting of a standard plastic seed tray (approximately 35cm × 25cm) lined with permeable horticultural fleece folded and stapled to be a good fit. Each trap was covered in plastic horticultural netting (black 1.5-cm mesh) and pegged to the ground below an oak tree (1-2 m from the trunk).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many designs of frass trap have been published (Liebhold & Elkington 1988, Seki & Takano 1998, Tinbergen 1960, Tinbergen & Dietz 1994, Zandt 1994, but in this study we deployed simple, inexpensive traps consisting of a standard plastic seed tray (approximately 35cm × 25cm) lined with permeable horticultural fleece folded and stapled to be a good fit. Each trap was covered in plastic horticultural netting (black 1.5-cm mesh) and pegged to the ground below an oak tree (1-2 m from the trunk).…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been many individual projects in Britain and elsewhere looking at the timing of the caterpillar peak (Maziarz & Wesol / / / / / owski 2010, Naef-Daenzer & Keller 1999, Perrins 1991, Seki & Takano 1998, Sisask et al 2010, van Balen 1973, Veen et al 2010, only in the Netherlands have extensive studies been reported , Both et al 2006. Variation in the abundance of defoliating caterpillars in woodlands can be measured by the volume of frass (the material that plant-eating insects pass as waste after digestion) which falls from the canopy (Tinbergen 1960, Tinbergen & Dietz 1994.…”
mentioning
confidence: 99%
“…Perrins 1965;Gosler 1993;Seki and Takano 1998). Pairs breeding earlier or later than the peak of food abundance should therefore tend to be less successful.…”
Section: Introductionmentioning
confidence: 96%
“…The main predators of caterpillars in forests are passerine birds (Kristin and Patocka, 1997), especially during the breeding season, when the proportion of caterpillars in the nestlings' diet can exceed 90% (Seki and Takano, 1998). During the rearing period, a Great Tit (Parus major L.) pair preys on approximately 15-20 thousand caterpillars (Török, 1998).…”
Section: Introductionmentioning
confidence: 99%